2020
DOI: 10.3390/cancers12061595
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Ubiquitin System in the Pathogenesis of Squamous Cell Carcinomas

Abstract: The ubiquitin system is a dynamic regulatory pathway controlling the activity, subcellular localization and stability of a myriad of cellular proteins, which in turn affects cellular homeostasis through the regulation of a variety of signaling cascades. Aberrant activity of key components of the ubiquitin system has been functionally linked with numerous human diseases including the initiation and progression of human tumors. In this review, we will contextualize the importance of the two main components of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 204 publications
(262 reference statements)
0
8
0
Order By: Relevance
“…The ubiquitination pathway is widely involved in the regulation of cell cycle, proliferation, apoptosis, differentiation, damage repair, inflammation, immunity, and almost all other life activities [ 42 ]. Aberrant ubiquitin pathway has been functionally linked to the development and progression of many human diseases, including human tumors [ 43 ]. In lung cancer, it was reported that TRIM59 induced ABHD5 ubiquitination, leading to its proteasome-dependent degradation, whereas ABHD5 deficiency leads to metabolic reprogramming of macrophages and activation of NLRP3 inflammatory microsomes, generating an inflammatory environment for tumor development [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitination pathway is widely involved in the regulation of cell cycle, proliferation, apoptosis, differentiation, damage repair, inflammation, immunity, and almost all other life activities [ 42 ]. Aberrant ubiquitin pathway has been functionally linked to the development and progression of many human diseases, including human tumors [ 43 ]. In lung cancer, it was reported that TRIM59 induced ABHD5 ubiquitination, leading to its proteasome-dependent degradation, whereas ABHD5 deficiency leads to metabolic reprogramming of macrophages and activation of NLRP3 inflammatory microsomes, generating an inflammatory environment for tumor development [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitination of proteins is a common post-translational modification in most cell types. Disturbances of ubiquitin-mediated processes often result in tumorigenesis and metastasis, including lung cancer [ 99 – 101 ]. Ubiquitination is part of the mechanism leading to the dissociation of AJs during EMT [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic role of SKP2 reconciles with its overexpression in various human cancers including ovarian adenocarcinoma, breast cancer, lung cancer, colorectal cancer, prostate cancer, leukaemia and squamous cell carcinoma. 103 , 104 , 105 , 106 Interestingly, deletion of SKP2 has been shown to compensate for anti‐tumour and cell safeguarding deficiency in p53 deleted cancer cells due to elevated p27 levels. Zhao and co‐workers demonstrated this using SKP2 knockout mice and found that loss of p53 and pRB in these mice blocked tumorigenesis due to cell cycle arrest mediated by accumulated p27, suggesting that SKP2 could be a promising target for p53 mutant cancer therapy.…”
Section: Roles Of E3 Ligases In Cancer Hallmarksmentioning
confidence: 99%